PD-L1/PD-1 and CTLA-4 Expression in Equine Penile Squamous Cell Carcinomas - Porcellato, Ilaria (Animals (Basel), 2021)
SIMPLE SUMMARY: In the last few years, the treatment of different types of tumors in humans has benefited from the introduction of new drugs called “immune checkpoint inhibitors” (ICI). These treatments help the patient’s immune response in fighting against cancer, therefore limiting tumor growth and aggressiveness. The possibility to use this therapeutical strategy also in pet animals such as horses has been scarcely explored in veterinary medicine. This study aims at investigating the presence and expression of specific checkpoint molecules such as PD-L1 and CTLA-4 in penile tumors of horses, particularly regarding malignant squamous cell carcinomas. In fact, PD-L1 and CTLA-4 presence is pivotal for an effective response to ICI and a successful therapy. Unfortunately, our results seem to indicate that these molecules are not frequently expressed in equine penile tumors. Therefore, horses with penile tumors may not benefit from the therapeutical use of ICI. ABSTRACT: In horses, penile squamous cell carcinomas (epSCCs) are among the most common cutaneous neoplastic lesions. These tumors usually arise in benign lesions such as viral plaques and papillomas frequently induced by Equus caballus papillomavirus type 2 (EcPV2) infection. In the last decade, the introduction of immune checkpoint inhibitors (ICI) for the treatment of human cancers has demonstrated promising results. Among the most commonly targeted pathways, there is PD-1/PD-L1 and CTLA-4. The aim of this study is to investigate the expression of the PD-1/PD-L1 pathway and CTLA-4 in the tumor microenvironment of epSCCs to assess the feasibility of an immunotherapeutic approach. Twenty equine epithelial tumors were retrospectively selected and submitted to RT-qPCR for PD-1 and PD-L1 genes. After testing antibodies cross-reactivity by western blotting, immunohistochemistry for PD-L1 and CTLA-4 was performed. Results from RT-qPCR demonstrated that 3/20 cases expressed the PD-L1 gene, whereas the PD-1 gene was not detected. Immunohistochemical positivity for PD-L1 was found only in one case. CTLA-4-positive cells were observe in all cases but were few (Mdn = 4.8; IQR = 2.3–7.1 cells/HPF). In this study group, PD-1/PD-L1 and CTLA-4 do not appear to be highly expressed and therefore the use of ICI in epSCCs may not have promising rates of response.